Developing Behavioral Coding to Understand Family Communication Breakdown in Dementia Care. (March 2022) - Coleman, Carissa K.; Aly, Iman M.; Dunham, Ashlyn; Inderhees, Kacie; Richardson, Michaela; Wilson, Paige; Berkley, Amy; Savundranayagam, Marie; Williams, Kristine
Communication breakdown is a challenge for family caregivers of persons living with dementia. We adapted established theory and scales for computer-assisted behavioral coding to characterize caregiver communication for a secondary analysis. We developed verbal, nonverbal, and breakdown coding schemes and established reliability (κ > .85). Within the 221 family caregiving videos analyzed, 55% of exchanges were interactive, 30% were silence, 4% consisted of talking to self or others, and 8% included a breakdown. An average of 2.4 ( SD = 1.9) breakdowns occurred per observation and were successfully resolved 85% of the time, with 31% being resolved most successfully following only one flag and repair strategy. Caregivers were the primary speakers (67%); their communication preceded most breakdown (65%), and they primarily initiated the repairs after a breakdown (70%). Common repair strategies included clarifications (31%), asking questions (24%), and repeating information (24%). Associations between communication strategies and repair success will provide evidence for caregiver training.